A comprehensive review on phenol‐formaldehyde resin‐based composites and foams. Issue 12 (24th September 2022) - Ravindran, Lakshmipriya; M. S., Sreekala; Kumar S., Anil; Thomas, Sabu
Abstract: This article covers the introduction to polymer composites, phenol formaldehyde resin, phenol formaldehyde composites, and foams along with their properties and applications. The previous research in the fields of phenol formaldehyde composites, nanocomposites, and PF foams is also covered in depth. Various combinations of nanomaterials and processes have been investigated in the field of structural composites to meet the requirements of industries such as automotive, aerospace, military, civil, and construction. Due to their different features and possibilities when compared to equivalents composed of other polymers, particularly thermosets, phenol‐formaldehyde reinforced composites are commonly used for large load bearing structural applications. Composite properties can be improved by using nanoparticles, which are materials that have been developed as a result of advances in nanotechnology. This research focuses on a literature review of nanofillers' use to improve the structural properties of phenol‐formaldehyde composites and foams published in the last two decades. The use of nanomaterials to modify composites is examined in depth. Abstract :